TWO BURIALS OF THE BURIAL GROUND OF THE XIII-XV CENTURY SETTLEMENT «RAILWAY-2» (Krymsky district of Krasnodar territory) - Naroznyj, Evgenij Ivanovic; Tisenko, Igor' Borisovic (History, Archeology and Ethnography of the Caucasus, 2020)
the article introduces into scientific circulation two female graves (№94 and №177) OF the XIII-XIV centuries from the Lower prikuban (burial ground of the settlement "Railway-2". The burial inventory of burials fully characterizes the main lifetime occupations of the buried. These are shearing sheep, processing wool, making wool threads and tailoring. The most expressive are the earrings from burial # 177. They - with an asymmetric metal bead, are a variant of chernoklobutskih jewelry. Jewelry becomes another argument in favor of the version about the migration of these nomads from porosya to the North Caucasus, where they gradually "dissolve" in the local ethno-cultural environment.
Keywords: North Caucasus; Lower Kuban; Golden Horde; black hoods; Polovts; Georgia and the North Caucasus; the Golden Horde of the Volga region.